Predicting suicidality in late‐life depression by 3D convolutional neural network and cross‐sample entropy analysis of resting‐state fMRI - Lin, Chemin; Huang, Chih‐Mao; Chang, Wei; Chang, You‐Xun; Liu, Ho‐Ling; Ng, Shu‐Hang; Lin, Huang‐Li; Lee, Tatia Mei‐Chun; Lee, Shwu‐Hua; Wu, Shun‐Chi (Brain and behavior, 2024)
Background: Predicting suicide is a pressing issue among older adults; however, predicting its risk is difficult. Capitalizing on the recent development of machine learning, considerable progress has been made in predicting complex behavior such as suicide. As depression remained the strongest risk for suicide, we aimed to apply deep learning algorithms to identify suicidality in a group with late‐life depression (LLD). Methods: We enrolled 83 patients with LLD, 35 of which were non‐suicidal and 48 were suicidal, including 26 with only suicidal ideation and 22 with past suicide attempts, for resting‐state functional magnetic resonance imaging (MRI). Cross‐sample entropy (CSE) analysis was conducted to examine the complexity of MRI signals among brain regions. Three‐dimensional (3D) convolutional neural networks (CNNs) were used, and the classification accuracy in each brain region was averaged to predict suicidality after sixfold cross‐validation. Results: We found brain regions with a mean accuracy above 75% to predict suicidality located mostly in default mode, fronto‐parietal, and cingulo‐opercular resting‐state networks. The models with right amygdala and left caudate provided the most reliable accuracy in all cross‐validation folds, indicating their neurobiological importance in late‐life suicide. Conclusion: Combining CSE analysis and the 3D CNN, several brain regions were found to be associated with suicidality. Predicting suicide in older adults is difficulty. Using machine learning, we can predict suicidality from the certain brain regions' complexity of the resting state fMRI data.